Implementasi Program "Prosper Africa Initiative" Amerika Serikat Dalam Pembangunan Sektor Agribisnis Di Afrika - Tasya Mysheta (2022)
ABSTRACT Africa is a continent that is developing faster than any other continent in the world. With this acceleration, Africa could double its population in the future, and this poses a challenge for Africa to meet the needs of its population, as well as the development of the continent. However, in the future, Africa has great potential. Africa is also blessed with abundant natural resources, but the reality is that Africa is still not able to utilize existing natural resources and needs assistance for its development. The United States is one of the developed countries that has put its interests at stake by launching the Prosper Africa Initiative during the Trump administration, which officially took effect in 2019. This study aims to see how the US Prosper Africa program is implemented in Africa, which is seen from the agribusiness sector in Nigeria and Kenya as African countries that receive the program. The concept used by the author is the concept of public policy, food security, and foreign aid which is used by the author to help see the progress of the US Prosper Africa in Africa. The research method used in this study is descriptive qualitative which will describe the running of the Prosper Africa program in Africa with secondary data sources that will support this research. The results of the study show that the running of Prosper Africa provides a great opportunity for the US-Africa, which is supported by 17 US agencies and departments to assist the existing agreement. In Nigeria, Prosper Africa has increased added value for the agribusiness sector, especially for the tomato processing industry. In Kenya, Prosper Africa has also helped to increase technological capabilities in the agricultural sector, especially in water systems (irrigation). However, the existence of Prosper Africa is also a manifestation of US interests to be achieved in Africa. Keywords: United States, Prosper Africa Initiative, Agribusiness Sector, Africa.